PROSPEK PEMBENTUKAN ASEAN INTERGOVERNMENTAL COMMISSION ON HUMAN RIGHTS (AICHR) (Harapan Baru, Kelemahan dan Solusi) - Hadi Purwandoko, Prasetyo; Sasmini, Sasmini (Yustisia, 2012)
ABSTRACTASEAN Charter gives new expectation for the protection of human rights in ASEAN. One of the innovations contained in the ASEAN Charter is a provision regulating the promotion and protection of human rights. Regulations concerning the promotion and protection of human rights contained in the preamble, purposes, principles and Article 14 of the ASEAN Charter. ASEAN finally recorded a new history in an effort to promote and protect human rights s15by signing the Terms of Reference (TOR) of ASEAN Intergovernmental Commission on Human Rights (AICHR) as a result of the implementation of the 15th ASEAN Summit to held in Hua Hin , Thailand. However, the formation of AICHR still not perfect. There are a number of weaknesses and challenges that must be completed by the ASEAN countries, especially concerning the strengthening of the mandate and functions of AICHR on human rights protection.ABSTRAKPiagam ASEAN memberikan harapan baru  bagi perlindungan hak asasi manusia di ASEAN. Salah satu inovasi yang terkandung dalam Piagam ASEAN adalah ketentuan yang mengatur pengembangan  dan perlindungan hak asasi manusia. Peraturan mengenai pengembangan  dan perlindungan hak asasi manusia yang terkandung dalam pembukaan, tujuan, prinsip, dan Pasal 14  Piagam ASEAN. ASEAN akhirnya mencatat sejarah baru dalam upaya untuk mempromosikan/mengembangkan  dan melindungi hak asasi manusia dengan menandatangani Kerangka Acuan (TOR) of ASEAN Intergovernmental Commission on Human Rights (AICHR)   sebagai pelaksanaan KTT-15 ASEAN yang akan diadakan di Hua Hin, Thailand. Namun, pembentukan AICHR tidak/belum sempurna . Ada sejumlah kelemahan dan tantangan yang harus diselesaikan oleh negara-negara ASEAN, khususnya pada penguatan mandat dan fungsi AICHR tentang Perlindungan Hak Asasi Manusia.